Grãos em carbonatos marinhos cretácicos da Bacia Potiguar: formações Ponta do Mel e Jandaíra - Okubo, Juliana [UNESP] (2011)
This work aims to identify and photograph grains that compose important Cretaceous carbonate units of the Potiguar Basin, represented by the Ponta do Mel and Jandaíra formations (Albian-Campanian). Petrographic investigation of thin sections was essential. The samples studied come from wells and surface samples from the collection UNESPetro – UNESP, Rio Claro. In the Ponta do Mel Formation, the grains consist of ooids, oncoids, peloids and bioclasts. Regarding to the identified bioclasts, the solenoporacean red algae, mollusks (bivalves and gastropods), echinoids, foraminifera, ostracods and worms were the dominant elements. In the Jandaíra Formation, the grains are composed by ooids, peloids and bioclasts, which are represented by green algae, mollusks (bivalves and gastropods), benthic foraminifera miliolids, worms, echinoderms and ostracods. The grains found in the Ponta do Mel Formation are somewhat similar to those found in the Jandaíra Formation, with the exception of calcareous algae. The subsurface material from the Ponta do Mel Formation is derived from the upper part of the unit, representing marine high-energy carbonates, which also contains ooids and Trocholina. The samples of Jandaíra Formation, collected in outcrops, often contain green algae, mollusks and miliolids, and come from inner shelf and lagoon facies previously described